Dual silencing of the EGF and type 1 IGF receptors suggests dominance of IGF signaling in human breast cancer cells. - Riedemann, J; Sohail, M; Macaulay, V (2007)
Signaling via the type 1 insulin-like growth factor receptor (IGF1R) confers resistance to EGF receptor (EGFR) inhibitors. It is plausible that reciprocal EGFR compensation could mediate resistance to IGF1R inhibition, prompting us to investigate effects of IGF1R depletion on EGFR signaling in breast cancer cells expressing relatively high (MDA-MB-468) or low (MCF7) EGFR. Transient IGF1R knockdown induced enhanced phosphorylation of the EGFR and its effectors JNK, ERKs and STAT5, but this did not prevent apoptosis induction and inhibition of clonogenic survival following IGF1R knockdown. We used IGF1R shRNA to induce chronic IGF1R depletion, and achieved stable gene silencing in MCF-7 cells; here, EGFR overexpression led to EGFR hyperphosphorylation, again without abrogating survival inhibition after IGF1R knockdown. In both cell lines, dual receptor knockdown prevented EGFR hyperphosphorylation, but induced no greater inhibition of clonogenic survival than IGF1R knockdown alone. These results suggest that the EGFR cannot compensate for IGF1R depletion, and are encouraging for the strategy of IGF1R targeting.